致死的肺血栓塞栓症を来した外来ギプス治療中単独下肢外傷の2症例(A report of two outpatients presenting with fatal pulmonary thromboembolism resulting from lower limb immobilization by plaster cast after an isolated lower limb injury). Issue 3 (March 2015) - (Nobuo Sasaki), 佐々木 庸郎; (Takeaki Imamura), 今村 剛朗; (Takeo Matsuyoshi), 松吉 健夫; (Kazumasa Yamaguchi), 山口 和将; (Naoki Kojima), 小島 直樹; (Hiroshi Inagawa), 稲川 博司; (Yasusei Okada), 岡田 保誠
ABSTRACT: Venous thromboembolism (VTE) has been estimated to be one of the most common cardiovascular diseases in western countries, while Asians have been reported to have a lower risk for VTE. However, an increasing incidence of VTE has been observed in Japan, to which westernization of lifestyle, aging of the population, and increasing awareness of VTE have contributed. Patients with lower limb immobilization undergoing orthopedic surgeries have been reported to have the highest perioperative risk for VTE; thus, prophylactic anticoagulation is universally accepted and implemented. However, the preventive strategies for outpatients with lower limb immobilization by plaster cast differ among countries. Two outpatients recently presented to our institution with fatal pulmonary thromboembolism secondary to deep vein thrombosis resulting from lower limb immobilization by plaster cast after an isolated lower limb injury. One fully recovered after cardiac arrest, but the other died of cerebral edema. Despite of an increasing incidence of VTE in Japan, it appears that insufficient attention has been paid to outpatients with lower limb immobilization by plaster cast as a population with significant risk for VTE. Therefore, our report of these two cases demonstrates that outpatients with lower limb immobilization by plaster cast have a significant risk for VTE.